Nanowires of silver-polyaniline nanocomposite synthesized via in situ polymerization and its novel functionality as an antibacterial agent - Tamboli, Mohaseen S.; Kulkarni, Milind V.; Patil, Rajendra H.; Gade, Wasudeo N.; Navale, Shalaka C.; Kale, Bharat B. (Colloids and Surfaces B-Biointerfaces, 2012)
Silver-polyaniline (Ag-PANI) nanocomposite was synthesized by in situ polymerization method using ammonium persulfate CAPS) as an oxidizing agent in the presence of dodecylbenzene sulfonic acid (DBSA) and silver nitrate (AgNO3). The as synthesized Ag-PANI nanocomposite was characterized by using different analytical techniques such as UV-visible (UV-vis) and Fourier transform Infrared spectroscopy (FT-IR), field emission scanning electron microscopy (FE-SEM), thermo gravimetric analysis (TGA). X-ray diffraction (XRD), and transmission electron microscopy (TEM). UV-visible spectra of the synthesized nanocomposite showed a sharp peak at similar to 420 nm corresponding to the surface plasmon resonance (SPR) of the silver nanoparticles (AgNPs) embedded in the polymer matrix which is overlapped by the polaronic peak of polyaniline appearing at that wavelength. Nanowires of Ag-PANI nanocomposite with diameter 50-70 nm were observed in FE-SEM and TEM. TGA has indicated an enhanced thermal stability of nanocomposite as compared to that of pure polymer. The Ag-PANI nanocomposite has shown an antibacterial activity against model organisms, a gram positive Bacillus subtilis NCIM 6633 in Mueller-Hinton (MH) medium, which is hitherto unattempted. The Ag-PANI nanocomposite with monodispersed AgNPs is considered to have potential applications in sensors, catalysis, batteries and electronic devices. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: antibacterial activity; Conducting poly(aniline); In situ polymerization; Nanocomposite